To condone, condemn, or 'no comment'? Explaining a patron's reaction to a client's unilateral provocations. (May 2020) - Kim, Jeehye; Ko, Jiyoung
What explains a patron's decision to publicly condone, condemn, or forgo commenting on its client's unilateral provocations? We present a new theoretical framework that identifies a patron's two strategic considerations – maximizing its sphere of influence and avoiding entanglement – and factors that affect them. We claim that whenever a patron faces a great power rivalry or a vulnerable client, it is more likely to condone its client's provocations in order to safeguard its sphere of influence. On the other hand, when the risk of escalation looms large, the patron is more likely to condemn its client's provocations in order to avoid entanglement. Focusing on the Sino-North Korean patron–client relationship, we test our theory on an original dataset that tracks China's official reactions to provocations initiated by North Korea. We find that China tends to condone North Korea's provocations when the USA criticizes them, and refrains from condemning when North Korea is domestically fragile. We also find that China is more likely to condemn its client's provocations in the period after North Korea became a nuclear state. In addition, we draw on examples from the USA–Pakistan and the USA–Israel patron–client relationships to illustrate our causal logic. This article offers new insights on how a patron manages its client's unruly behavior, and provides the first large-N evidence on China's responses to North Korean provocations from 1981 to 2016.